A multi-objective optimization framework for assessing military ground vehicle design for safety. (January 2014) - Hoffenson, Steven; Arepally, Sudhakar; Papalambros, Panos Y
In recent years, the greatest safety threat to military personnel has been from underbody vehicle blast events, but other major threats exist against fuel convoys and due to rollover events. Ground vehicle designers make choices that affect one or more of these risk areas, including the weight and structural design of the vehicle underbody, as well as the design of seating systems that cushion the occupants from the rapid accelerations caused by blast loading. This study uses mathematical and computational tools to evaluate underbody blast, fuel convoy, and rollover safety criteria, and the models are combined into a multi-objective design optimization formulation that minimizes personnel casualties. The models and framework are highlighted and described in detail, and preliminary optimization results are presented under various conditions. The multi-objective behavior of the design problem is explored through weighted-objective Pareto frontiers, and the utility of the model in real-world situations is discussed.